A comparison of biomechanical models for MRI to digital breast tomosynthesis 3D registration - Cotič Smole, Patricia; Kaiser, Clemens G.; Krammer, Julia; Ruiter, Nicole; Hopp, Torsten (Computational biomechanics for medicine, 2019)
Increasing interest in multimodal breast cancer diagnosis has led to the development of methods for MRI to X-ray mammography registration. The severe breast deformation in X-ray mammography is often tackled by biomechanical models, yet there is no …